(untitled) (American Journal of Islam and Society, 1991)
This issue, like all the previous ones, opens with ‘AbdulHamid AbQSulaymsn’s “Guiding Light.” But this time we have given it a subtitle and would like to invite our readers’ attention to the important issue addressed here. AbiiSulaymSin quotes the Qur’an and the hadith to show that the constitutional process of political authority and government in Islam is shiirii -decision making through consultation. The individual is required to participate seriously in the shuratic process and enjoin what is good and oppose what is evil through peaceful means. The Qur’an, AbQSulaymh asserts, requires patience and peaceful struggle in the face of internal oppression and dissension, but authorizes the oppressed to fight and use force against outside aggression and occupation. Internally, force and violence have no place in solving political issues within the ummah. We hope that the author’s conclusion will initiate a discussion, and we encourage our readers to respond. This is followed by Louay M. Safi‘s article on the purpose of an Islamic state, its source of political legitimacy, and the scope of state power. He argues that a clear distinction should be made between the role and purpose of the state and those of the ummah. Only through such a separation of objectives, writes Safi, we can properly observe the injunctions of the Shari‘ah and the principles of revelation. An Islamic state, according to Safi, should be identified with the system of rules determining the quality of life in the political organs necessary for the realization of Islamic ideals. Such an entity naturally presupposes a society committed to Islamic principles and norms. Eric A. Winkel deals with the paradigm shifts in political science in the postmodern debate. Beginning with Kuhn’s belief that paradigm shifts are mainly passive and the natural result of people realizing that the present prevalent paradigm contains some anomalies, a belief which he does not share, Winkel goes on to show how that paradigm supports the ruling elite. This line is continued in his analysis of the views of Ashley and Gilpin, who are representatives of opposing viewpoints. Taking the modern Western paradigm, which is built on a scientific worldview and self-interest, he shows how this construct has been used to propagate the idea that the West has reached the pinnacle of civilization due to its scientific superiority vis-‘a-vis the rest of the world. He then looks at what the West has done with its advancement: genetic engineering (in effect changing reality to suit its desires), relegating ...